Dichroic Sb2O3/Ag/Sb2O3 Electrodes for Colorful Semitransparent Organic Solar Cells. Issue 9 (6th July 2020) - Song, Seyeong; Cho, Hye Won; Jeong, Jaeki; Yoon, Yung Jin; Park, Song Yi; Song, Suhee; Woo, Byung Hoon; Jun, Young Chul; Walker, Bright; Kim, Jin Young
Abstract : The pace of advancement and increasing power conversion efficiencies (PCEs) have provided the possibility for organic solar cells (OSCs) to be commercialized in a variety of applications, including semitransparent photovoltaics. The application of dielectric–metal–dielectric (DMD) transparent electrodes to OSCs is an effective way to achieve semitransparent OSCs with different colors. Herein, a DMD multilayer structure based on two Sb2 O3 layers and silver (Ag) thin films as the top electrode is introduced. An ultrathin Sb2 O3 layer is deposited between the electron transport layer and the Ag film as a bottom layer for the Sb2 O3 /Ag/Sb2 O3 electrode; this layer inhibits Ag atom diffusion and aggregation, which leads to uniform formation of ultrathin Ag films. The thickness of the middle metal layer influences fill factor and short‐circuit current density values, which correlate well with device resistance and light reflection. For the top Sb2 O3 layer, the thickness allows the selective transmittance of specific wavelengths of visible light while reflecting wavelengths that are not transmitted, creating a dichroic effect. OSCs are successfully fabricated using three kinds of colorful active layers in conjunction with Sb2 O3 /Ag/Sb2 O3 electrodes, resulting in vividly colored devices with PCE of 6.33–7.88% and average visible transmittances of 23–30%. Abstract : Sb2 O3 /Ag/Sb2 O3 multilayer electrodes are used in organic solar cells (OSCs) to demonstrate colorful semitransparent devices. Notably, the effect of thickness of each layer in the electrode on the optical properties and performance of organic solar cells is thoroughly investigated. By matching the electrodes with the absorption characteristics of the active layers, esthetically colored, semitransparent OSCs can be fabricated.